О результатах испытания экспериментального образца ствола ручного пожарного универсального СПРУ-50/0.7 - Shafranskiy, Дмитрий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The article describes results of tests and practical application of an experimental sample of a trunk of the universal manual fire barrel. A construction test stand, its characteristics, the climatic conditions during the test is described. According to tests, the conclusions have been given, and the changes of design documentations have been prepared.